Surgeons' posture and muscle strain during laparoscopic and robotic surgery. Issue 6 (10th January 2020) - Dalager, T; Jensen, P T; Eriksen, J R; Jakobsen, H L; Mogensen, O; Søgaard, K
Abstract: Background: It is assumed that conventional laparoscopy (LAP) and robotic-assisted laparoscopic surgery (RALS) differ in terms of the surgeon's comfort. This study compared muscle workload, work posture and perceived physical exertion of surgeons performing LAP or RALS. Methods: Colorectal surgeons with experience in advanced LAP and RALS performed one of each operation. Bipolar surface electromyography (EMG) recordings were made from forearm, shoulder and neck muscles, and expressed relative to EMG maximum (%EMGmax ). The static, median and peak levels of muscle activity were calculated, and an exposure variation analysis undertaken. Postural observations were carried out every 10 min, and ratings of perceived physical exertion before and after surgery were recorded. Results: The study included 13 surgeons. Surgeons performing LAP showed higher static, median, and peak forearm muscle activity than those undertaking RALS. Muscle activity at peak level was higher during RALS than LAP. Exposure variation analysis demonstrated long-lasting periods of low-level intensity muscle activity in the shoulders for LAP, in the forearms for RALS, and in the neck for both procedures. Postural observations revealed a greater need for a change in work posture when performing LAP compared with RALS. Perceived physical exertion was no different between the surgical modalities. Conclusion: Minimally invasive surgery requires long-term static muscle activity with a high physical workload for surgeons. RALS is less demanding on posture. Graphical Abstract: This study showed that minimally invasive surgery involves long-term static work posture, which poses a high physical workload on surgeons. LAP,  conventional laparoscopy; RALS, robotic-assisted laparoscopic surgery. Robotic may be more comfortable